Сучасні напрями розвитку індустрії туризму в Україні - Збарський, В. К.; Грибова, Діана Вікторівна; Грибова, Диана Викторовна; Hrybova, Diana (My University, 2020)
UK: У статті досліджено сучасний стан та особливості розвитку індустрії туризму в Україні. Зазначено роль зовнішніх факторів у процесі забезпечення ефективного розвитку туристичної індустрії. Висвітлено основні фактори, що сприяли зростанню виїзного туризму на Україні: введення безвізового режиму з країнами ЄС, розширення авіаперевезень та відкриття прямих авіарейсів, зростання кількості пропозицій низькобюджетних турів, зростання купівельної спроможності українців, зміцнення курсу національної валюти. Доведено, що важливою особливістю туристичного бізнесу є залежність від різких сезонних коливань попиту на туристичний продукт. Для розрахунку впливу сезонної компоненти розраховано індекси сезонності — відсоткові відношення середніх місячних рівнів за ряд років до загального середньомісячного обсягу виїздів громадян за весь розрахунковий період. За результатами досліджень доведено, що виїзний туризм в Україні має яскраво виражену сезонність. Відмічається подальше зростання попиту на виїзний туризм, що в майбутньому забезпечуватиме ще більший відтік валюти, який негативно позначиться на платіжному балансі країни і на рівні валового внутрішнього продукту. Визначено основні тенденції в контексті дії рівня доходів населення на розвиток виїзного туризму. Зазначається, що країни з високим рівнем доходів населення, з одного боку, генерують більший туристичний потік, а з іншого є більш привабливими для туристів за країни з низьким рівнем життя. Доведено, що такий фактор є чинником купівельної спроможності потенційних українських туристів. EN: The article investigates the current state and features of the development of the tourism industry in Ukraine. It is proved that during the independence of Ukraine there was a significant development of the tourism industry, but the general trends of the ratio of the three main types of tourism remained stable. The necessity to study the current state and features of the tourism industry in Ukraine is substantiated. The role of external factors in the process of ensuring the effective development of the tourism industry is outlined. The main factors that contributed to the growth of outbound tourism in Ukraine are highlighted: the introduction of a visa-free regime with EU countries, the expansion of air travel and the opening of direct flights, the increase in the number of low-budget tours, the increase of the purchasing power of Ukrainians, the strengthening of the national currency. It is proved that an important feature of the tourism business is the dependence on the sharp seasonal fluctuations in demand for the tourism product. To calculate the impact of the seasonal component, seasonality indices have been calculated — the percentage of average monthly levels for a number of years to the total average monthly output of citizens for the entire accounting period. According to the results of the research it is proved that outbound tourism in Ukraine has a pronounced seasonality. The peak season of outbound tourism is in June, July and August. The maximum demand is observed in August, the minimum value is observed in February. There is a further increase in demand for outbound tourism, which in the future will provide even more outflow of currency, which will negatively affect the balance of payments of the country and the level of gross domestic product. It is proved that the established tendency of development of the tourist industry of the country will not provide benefit to the national economy, and therefore the brand of Ukraine as a tourist country. The main trends in the context of the impact of the level of income on the development of outbound tourism are identified. It is noted that high-income countries, on the one hand, generate more tourist flow and, on the other, are more attractive to tourists than low-living countries. It is proved that this factor is a factor in the purchasing power of potential Ukrainian tourists.
Modern directions of the tourism industry development in Ukraine
Keywords: туристична індустрія; тренди розвитку; виїзний туризм; ефективність; туристичний потік; tourism industry; development trends; outbound tourism; efficiency; tourist flow